Responsibility of the Default Debtor in the Implementation of the Credit Agreement and Settlement - Susinta Yasin; Wen Almoravid Dungga; Julius T Mandjo (Universitas Negeri Gorontalo, 2022)
This article discusses the provision of credit provided by banks, one of which is at the Telaga Unit BRI bank with a building guarantee. Where at the Telaga Unit BRI bank in providing credit previously preceded by an agreement. To enter into an agreement, the borrower (customer) must have collateral. Without collateral, a customer cannot obtain a loan because collateral is one of the requirements for the customer to enter into a loan agreement. There is a close relationship between the lender and the guarantee. To guarantee repayment of credit from the debtor.